Brand governance practices in Canadian national sport organizations: an exploratory study - Taks, Marijke; Seguin, Benoit; Naraine, Michael L.; Thompson, Ashley; Parent, Milena M.; Hoye, Russell (Université d'Ottawa | University of Ottawa, 2019)
Research Questions: We explored if and how decision-makers of different types of national sport organizations (NSOs) govern their brand, considering the changing landscape and the role of stakeholders and social media. The three research questions were: (RQ1) Do leaders of NSOs include brand governance in their overall governance?; (RQ2) How important is the relationship between the NSOs and their stakeholders for NSOs’ brand governance?; (RQ3) How does social media contribute to NSOs’ brand governance? Research methods: Thirty-two chief executive officers (CEOs) and/or board members of 58 Canadian NSOs (RR=55%) participated in an online survey. Data were collected about brand governance in the organization (8 questions), the interrelationship with stakeholders (4 questions), and the role of social media in brand governance (4 questions). Results and findings: Brand governance is absent in small NSOs, and in early stages of application by larger NSOs. NSOs deal with their brand primarily internally, with no operational involvement of stakeholders, missing opportunities for possible knowledge transfer and co-creation to help NSOs govern their brand. Social media is a cost-efficient way to brand the organization, but a lack of control and consistency indicates a need for brand governance related to social media. Implications: NSOs would benefit from actively involving stakeholders to co-create and strengthen their brand. Social media offers opportunities for branding, but governance regulations should help overcome major challenges. Future research should include 3 interviews with NSOs’ decision-makers to further understand how NSOs can engage more meaningfully with stakeholders and social media to strengthen their brand governance.